The why (not) and how (not) of survey to digital footprint linkages: a use-case of ethnic background and social relationships. - Hofstra, Bas (Journal of Ethnic & Migration Studies, 2025)
In the last decade, there has been a rise of mixed-method-big data approaches in the social sciences. One such approach is linking survey data with digital footprint data. Yet, some of the fundamental challenges of linking survey data with digital footprint data are often unaddressed in prior work. Yet especially because of the importance of ethnic background dynamics in social relationships and the opportunities that survey/digital footprint data linkages afford, addressing such challenges is key. This is because statistical and methodological errors compound and are reinforced when one links (selective) data sources; or when social categories in footprint data are not as detailed as they could be. This contribution lays out why linking survey data with digital footprint data provides insights into ethnic inequalities and intergroup social cohesion, yet simultaneously addresses some of the challenges of doing so with a particular use-case as an example. Consequently, this contribution provides case-examples of methodologies for linking survey and footprint data – i.e. how to be aware of and account for sampling bias, and how to extract meaning in the context of ethnic background from unstructured data.